Clonal diversity and T-cell receptor beta-chain variable gene expression in enlarged lymph nodes of MRL-lpr/lpr lupus mice. - Singer, P A (1986)
The autosomal recessive lpr gene accelerates a systemic lupus erythematosus-like disease in genetically predisposed mice and induces autoantibodies in mice of normal genetic background. The molecular mode(s) of action of the lpr gene and its chromosomal location remain unknown, but it is primarily expressed as a massive T-cell proliferation manifested only in the presence of a thymus. To define the clonal diversity and maturational stage of the abnormally proliferating T cells found in enlarged lymph nodes of MRL-lpr/lpr mice, and their possible role in autoreactive B-cell activation, we analyzed their T-cell receptor beta-chain variable region (V beta) gene sequences. Twenty-five VDJ-containing beta-chain cDNA sequences were examined, each of which was found to derive from a distinct rearrangement in the correct reading frame, yielding translatable beta-chain mRNAs. An additional 10 clones were derived from truncated nonfunctional mRNAs. D beta 1 and D beta 2 elements were used equally in the sequenced clones, and 10 of the possible 12 mouse J beta elements were represented. Remarkably, 60% of the functional beta-chain mRNAs expressed V beta 8.2 or V beta 8.3 genes, whereas the equally homologous V beta 8.1 gene was not represented at all. Other V beta genes were found at lower frequencies in the library, including one previously unidentified V beta gene. The results indicate that the clonal makeup of the abnormally proliferating lymph node T cells in MRL-lpr/lpr mice is heterogeneous, but V beta gene expression is significantly skewed in favor of V beta 8.2/8.3 genes. The preferential representation of V beta 8 genes might be caused by lpr gene-induced modification of T-cell thymic processing and relate to the lpr gene-associated autoimmunity.